2011
DOI: 10.3917/geco.103.0026
|View full text |Cite
|
Sign up to set email alerts
|

Les transitions professionnelles contraintes par des restructurations : dynamiques individuelles et modalités d'accompagnement

Abstract: Les restructurations sont devenues quasi permanentes dans de nombreuses grandes entreprises soumises à des mutations profondes. Ce phénomène renforce le besoin d’accompagnement des reclassements et des trajectoires professionnelles. Cet article cherche à mieux saisir la manière dont les individus soumis à des transitions professionnelles contraintes peuvent reconstruire une trajectoire professionnelle et à dégager des conditions permettant à des dispositifs d’accompagnement de faciliter cette reconstruction. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…Dans ce cas, ils relèvent davantage du vécu expérientiel de l'individu, et l'accumulation d'émotions négatives pourrait être considérée comme élément prédisant une reconversion. Parfois, ils sont liés au contexte organisationnel ou sociétal et correspondent à des restructurations (Berton, 2013 ;Sardas & Gand, 2011), des délocalisations (Vignal, 2005), une dégradation des conditions de travail (Gollac, 2005), des conflits (Glée & Scouarnec, 2009) ou des plans sociaux (Mazade, 2003). Des imprévus comme une maladie ou un accident du travail sont également reconnus comme causes de transition et de reconversion professionnelle (Waser & Lenel, 2014).…”
Section: éVénements Déclencheurs De Reconversion Et D'émotionunclassified
“…Dans ce cas, ils relèvent davantage du vécu expérientiel de l'individu, et l'accumulation d'émotions négatives pourrait être considérée comme élément prédisant une reconversion. Parfois, ils sont liés au contexte organisationnel ou sociétal et correspondent à des restructurations (Berton, 2013 ;Sardas & Gand, 2011), des délocalisations (Vignal, 2005), une dégradation des conditions de travail (Gollac, 2005), des conflits (Glée & Scouarnec, 2009) ou des plans sociaux (Mazade, 2003). Des imprévus comme une maladie ou un accident du travail sont également reconnus comme causes de transition et de reconversion professionnelle (Waser & Lenel, 2014).…”
Section: éVénements Déclencheurs De Reconversion Et D'émotionunclassified
“…This might include helping define a professional project, conducting job-role analysis (Krumboltz, 2015; Paul and Moser, 2009), or assisting with writing a CV. The consultant must demonstrate a capacity for professional guidance (Sardas and Gand, 2011). The psychological approach: research has demonstrated the damaging effects of redundancy – it can lead to negative psychological effects such as anxiety, a sense of loss, and/or a feeling of betrayal (Krumboltz et al , 2013).…”
Section: Accompanying Career Transitionmentioning
confidence: 99%
“…This might include helping define a professional project, conducting job-role analysis (Krumboltz, 2015; Paul and Moser, 2009), or assisting with writing a CV. The consultant must demonstrate a capacity for professional guidance (Sardas and Gand, 2011).…”
Section: Accompanying Career Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…We would however go further by arguing that if roles contribute to processes of identity building, identity work is only one of the dimensions of individuals' response to the prescriptions associated to their role. The interest of such an approach is its ability to shed light on a comprehensive set of dimensions core to understanding individual experiences at work, which include but are not restricted to their sense of identity and belonging, by taking simultaneously into account, for example, the strategic resources individuals have to face expectations, their physiological resistance, their cognitive ability to do what they are asked and their subjective perception of role expectations (Sardas, 2008;Sardas, Dalmasso, & Lefebvre, 2011;Sardas & Gand, 2011). The role approach will allow us to gather insights into how expectations shape individual behaviour but also into how role enactment can question and shape the organisation in return.…”
Section: Draws Onmentioning
confidence: 99%